2020
DOI: 10.3390/ijms21197048
|View full text |Cite
|
Sign up to set email alerts
|

ND-13, a DJ-1-Derived Peptide, Attenuates the Renal Expression of Fibrotic and Inflammatory Markers Associated with Unilateral Ureter Obstruction

Abstract: DJ-1 is a redox-sensitive chaperone with reported antioxidant and anti-inflammatory properties in the kidney. The 20 amino acid (aa) peptide ND-13 consists of 13 highly conserved aas from the DJ-1 sequence and a TAT-derived 7 aa sequence that helps in cell penetration. This study aimed to determine if ND-13 treatment prevents the renal damage and inflammation associated with unilateral ureter obstruction (UUO). Male C57Bl/6 and DJ-1−/− mice underwent UUO and were treated with ND-13 or vehicle for 14 days. ND-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…In vivo, Park7 deficiency aggravated UUO-induced renal fibrosis, as manifested by more severe tubular atrophy and kidney deposition of extracellular matrix proteins in Park7 ko mice than in WT mice following UUO (Figure 2). Consistently, the latest work by Miguel et al demonstrated the inhibitory effect of ND-13 (PARK7 peptide) on UUO-induced renal fibrosis (36). Collectively, these studies indicate that renal tubular cell PARK7 has an anti-fibrotic, protective function in kidney diseases.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In vivo, Park7 deficiency aggravated UUO-induced renal fibrosis, as manifested by more severe tubular atrophy and kidney deposition of extracellular matrix proteins in Park7 ko mice than in WT mice following UUO (Figure 2). Consistently, the latest work by Miguel et al demonstrated the inhibitory effect of ND-13 (PARK7 peptide) on UUO-induced renal fibrosis (36). Collectively, these studies indicate that renal tubular cell PARK7 has an anti-fibrotic, protective function in kidney diseases.…”
Section: Discussionsupporting
confidence: 64%
“…ND-13 is PARK7-based peptide that has been shown be cytoprotective under stressful conditions, such as Cerebral reperfusion injury (32). Miguel et al showed that UUO mice received ND-13 (3 mg/kg of body weight) via subcutaneous injection starting from the day of surgery, daily for 14 days showed reduced expression of fibrotic and inflammatory markers compared to UUO mice received vehicle, suggesting a beneficial effect of ND-13 in renal fibrosis (36). In the present study, administration of ND-13 (2 mg/kg of body weight) via tail veil injection starting from the day after surgery, daily for 7 days reduced the renal levels of Tgfb mRNA, Tnfa mRNA and infiltration of macrophages into kidney tissues (Figures 8G-J).…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether DJ-1 affects microglial/macrophage polarization and participates in the inflammatory response, we used ND13 (DJ-1 based peptide) ( Glat et al, 2016 ; Molcho et al, 2018 ; Miguel et al, 2020 ) and DJ-1 siRNA to produce an effect on DJ-1 expression. Then, we measured the expression of microglial cell marker proteins (pro-inflammatory markers: iNOS and CD86; anti-inflammatory markers: Arg1 and CD163) and the expression of inflammatory mediators by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…ND13 is a newly discovered polypeptide that consists of 13 DJ-1-derived amino acids and 7 TAT-derived amino acids ( Glat et al, 2016 ; Molcho et al, 2018 ; Miguel et al, 2020 ). ND13 has been reported to alleviate dopaminergic system dysfunction in a Parkinson’s disease model ( Longa et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation